Design, security and implementation of learning focal point algorithm in a docker container - Salah Eddine Mansour; Abdelhak Sakhi; Larbi Kzaz; Oussama Tali; Abderrahim Sekkaki (Institute of Advanced Engineering and Science, 2024)
Artificial intelligence is not smart enough. This is why we are looking for complementary algorithms in order to increase the performance of machine learning and neural networks (NN). We have innovated an algorithm called learning focal point (LFP). This algorithm will help us increase the intelligence of machine learning and the NN. In this article, we will present the algorithm in detail, starting with the mathematical and theoretical principles, passing through the development and deployment in cloud docker containers, and ending with the security of its application programming interface (API). Finally, we are going to do a test in which we apply it in the case of using tin cans.